The Limit of Rationality in Choice Modeling: Formulation, Computation, and Implications - Jagabathula, Srikanth; Rusmevichientong, Paat (Management Science, 2018)
Customer preferences may not be rational, so we focus on quantifying the limit of rationality (LoR) in choice modeling applications. We define LoR as the cost of approximating the observed choice f...